Differentiation of Thyroid Nodules Difficult to Diagnose With Contrast-Enhanced Ultrasonography and Real-Time Elastography - Xi, Xuehua; Gao, Luying; Wu, Qiong; Fang, Shibao; Xu, Jingzhu; Liu, Ruyu; Yang, Xiao; Zhu, Shenling; Zhao, Ruina; Lai, Xingjian; Zhang, Xiaoyan; Zhang, Bo; et al. (Frontiers in Oncology, 2020)
According to the 2015 American Thyroid Association (ATA) referred risk stratification, thyroid nodules with intermediate- and low-suspicion patterns are difficult to diagnose. The objective of this study is to evaluate the diagnostic performance of contrast- enhanced ultrasonography (CEUS) and elastosonography (ES) for differentiation of these thyroid nodules. From November 2011 to June 2016, a total of 163 thyroid nodules with intermediate- and low-suspicion patterns in 150 consecutive patients at our hospital were studied before surgery. With surgical pathology as the standard, the diagnostic value of CEUS and ES was analyzed. There were 29 (17.8%) malignant lesions and 134 (82.2%) benign lesions. The enhancement patterns of CEUS, the echogenicity and elastography were significantly different between malignant and benign lesions (P<0.05). Heterogeneous enhancement was more common in malignant nodules, and the sensitivity, specificity, positive predictive value, negative predictive value and odds ration were 51.7%, 88.1%, 48.4%, 89.4% and 10.1, respectively. The diagnostic accuracy of CEUS was better than conventional ultrasound (area under the curve, AUC 0.729 vs 0.616, P = 0.021). The enhancement patterns of CEUS were helpful in the differential diagnosis of thyroid nodules with intermediate- and low-suspicion.